Fe2Ni2N nanosheet array: an efficient non-noble-metal electrocatalyst for non-enzymatic glucose sensing. (14th August 2017) - You, Chao; Dai, Rui; Cao, Xiaoqin; Ji, Yuyao; Qu, Fengli; Liu, Zhiang; Du, Gu; Asiri, Abdullah M; Xiong, Xiaoli; Sun, Xuping; Huang, Ke
Abstract: It is very important to develop enhanced electrochemical sensing platforms for molecular detection and non-noble-metal nanoarray architecture, as electrochemical catalyst electrodes have attracted great attention due to their large specific surface area and easy accessibility to target molecules. In this paper, we demonstrate that an Fe2 Ni2 N nanosheet array grown on Ti mesh (Fe2 Ni2 N NS/TM) shows high electrocatalytic activity toward glucose electrooxidation in alkaline medium. As an electrochemical glucose sensor, such an Fe2 Ni2 N NS/TM catalyst electrode demonstrates superior sensing performance with a short response time of less than 5 s, a wide linear range of 0.05 μ M–1.5 mM, a low detection limit of 0.038 μ M (S/N = 3), a high sensitivity of 6250 μ A mM −1 cm −2, as well as high selectivity and long-term stability.